Sequencing‐Based Bin Map Construction of a Tomato Mapping Population, Facilitating High‐Resolution Quantitative Trait Loci Detection. Issue 1 (1st March 2019) - Gonda, Itay; Ashrafi, Hamid; Lyon, David A.; Strickler, Susan R.; Hulse‐Kemp, Amanda M.; Ma, Qiyue; Sun, Honghe; Stoffel, Kevin; Powell, Adrian F.; Futrell, Stephanie; Thannhauser, Theodore W.; Fei, Zhangjun; et al.
Abstract : Genotyping‐by‐sequencing (GBS) was employed to construct a highly saturated genetic linkage map of a tomato ( Solanum lycopersicum L.) recombinant inbred line (RIL) population, derived from a cross between cultivar NC EBR‐1 and the wild tomato S. pimpinellifolium L. accession LA2093. A pipeline was developed to convert single nucleotide polymorphism (SNP) data into genomic bins, which could be used for fine mapping of quantitative trait loci (QTL) and identification of candidate genes. The pipeline, implemented in a python script named SNPbinner, adopts a hidden Markov model approach for calculation of recombination breakpoints followed by genomic bins construction. The total length of the newly developed high‐resolution genetic map was 1.2‐fold larger than previously estimated based on restriction fragment length polymorphism (RFLP) and polymerase chain reaction (PCR)–based markers. The map was used to verify and refine QTL previously identified for two fruit quality traits in the RIL population, fruit weight (FW) and fruit lycopene content (LYC). Two well‐described FW QTL ( fw2.2 and fw3.2 ) were localized precisely at their known underlying causative genes, and the QTL intervals were decreased by two‐ to tenfold. A major QTL for LYC content ( Lyc12.1 ) was verified at high resolution and its underlying causative gene was determined to be ζ ‐carotene isomerase ( SlZISO ). The RIL population, the high resolution genetic map, and the easy‐to‐use genotyping pipeline, SNPbinner, are made publicly available.